Investigation of Thermoelectric Properties of P-Type GaN Thin Films. Issue 1774 (2015) - Kucukgok, Bahadir; Hussain, Babar; Zhou, Chuanle; Ferguson, Ian T.; Lu, Na
ABSTRACT: GaN and its alloys are promising candidates for high temperature thermoelectric (TE) materials due to their high Seebeck coefficient and high thermal and mechanical stability. Moreover, these materials can overcome the toxicity concern of current Te-based TE materials, such as Bi2 Te3 and PbTe. These materials have recently shown a higher Seebeck coefficient than that of SiGe in high temperature region because their large bandgap characteristic eliminates the bipolar conduction. In this study, we report the room temperature thermoelectric properties of p-type Mg doped GaN, grown by metalorganic chemical vapor deposition (MOCVD) on sapphire substrate with various carrier concentrations. Undoped and n-type GaN are also incorporated with p-type GaN films to make comparison. The structural, optical, electrical, and thermal properties of the samples were examined by X-ray diffraction, photoluminescence, van der Pauw hall-effect, and thermal gradient methods, respectively. The Seebeck coefficient ranging from 710-900µV/K at room temperature of Mg: GaN were observed, which further indicated their potential TE applications.